Automatic enrollment and employer match: an experiment with the choice of pension plans. Issue 3 (2nd June 2020) - Pereira, Antonio Gualberto; Afonso, Luís Eduardo
Abstract : Purpose: The purpose of this study is to identify arrangements of fully funded defined contribution (FF-DC) pension plans associated with the continuity of retirement savings. Design/methodology/approach: The authors adopted an experimental design composed of a control group and two treatment groups. In all groups, individuals made decisions throughout nine periods: five during the working period and four at the postretirement stage. The authors asked participants if they wanted to join a pension plan, and which plan. The authors offered three plans with different risk profiles: plan 1 (high risk), plan 2 (moderate) and plan 3 (low risk) and one risk-free plan, plan 4. In treatment groups 1 and 2, there was an automatic enrollment of the participants in the default plan (moderate risk), and in the following periods they had to decide whether to continue contributing, and in this case, to which plan, with a defined percentage. Findings: In treatment scenarios, participants chose the riskiest plan in all periods of the experiment, and most of them chose the risk-free plan in period 5. These findings suggest that pension plans with automatic enrollment, employer matching and low risk foster the continuation of retirement savings. Research limitations/implications: The research has as limitation the fact that the sample is not representative of the population and therefore does not allow generalizations. This is because the authors use social media ads to prospect respondents. Practical implications: The research's findings can be relevant for the design of public policies for private pension plans, suggesting that compulsory automatic enrollment can be used as default in plans offered by the employers. The results encourage the inclusion of behavioral elements in the design of the pension system, paying attention to the nudges. In this sense, it is possible to increase participation in the pension plan and develop low cost programs to increase the amount accumulated by people before retirement. Social implications: Decision-making architecture, such as automatic enrollment, can improve individuals' retirement decisions, affecting savings and welfare in the long run. Originality/value: Although the effect of pension plan designs is widely studied in other countries, such as the United States and United Kingdom, the authors are unaware of a national empirical research that seeks to understand how different arrangements affect an individual choice through an experiment.